Ninhydrin Loaded Microcapsules for Detection of Natural Free Amino Acid - Suhui Jeong; Yeji Jeon; Jaehun Mun; Se Min Jeong; Huiling Liang; Kyeongwoon Chung; Pyong-In Yi; Beum-Soo An; Sungbaek Seo (Chemosensors, 2023)
Natural free amino acids present in plant extracts or tea infusions provide a unique flavor and potential effect on anxiety and blood pressure reduction. Accordingly, quantifying free amino acids in foods has been of interest to food science and analytical research fields. The ninhydrin solution-based assay is a colorimetric method based on the formation and detection of Ruhemann’s purple complex. Media-based colorimetric detection requires specialized facilities and personnel; moreover, it can suffer from the interference of the analyte color. In this study, we developed ninhydrin-loaded microcapsules and a simple free amino acids detection procedure, by simply dipping the microcapsules into the analyte solution for 3 min. Among the five tested natural free amino acids, theanine exhibited the highest colorimetric response to microcapsule-based detection, with a limit of detection of 0.826 mM.